Masker Wajah Lobak Putih dan Madu Untuk Perawatan Kulit Kering - Agus Susanti; Emiziana (Garina, 2020)
Dry facial skin causes cracks on the skin surface and will feel dry to the touch. Dry skin is caused by genetic factors, aging, hormonal changes, and cold weather. The purpose of this study was to make a mask made from white radish and honey which functions to moisturize facial skin so that it can be used for dry facial treatment. The method used in this research is interview method, documentation, library method, experimental method. Experiments on making white radish and honey face masks for the treatment of dry skin were carried out at the Laboratory of the Kartini Academy of Social Welfare's Makeup Study Program, Jalan Sultan Agung, No. 77, Gajahmungkur Village, Gajah Mungkur District, Semarang. City. Experiments were carried out 3 times with the composition of 1) white radish 41.25 g, honey 35 g 2) white radish 41.25 g, honey 40 g 3) white radish 41.25 g honey 55 g. The results showed that the third experiment resulted in products: fresher aroma (honey scent), soft texture, dark brown color, stronger adhesion so that it is easy to apply. Implementing it properly supports amazing results. The change after 2 uses of White Radish and Honey Face Mask leaves skin moisturized and supple